Between Citizenship and Belonging: Transnational Ethnic Strategies of Muslim Arab Sudanese in the Diaspora - Fábos, Anita (Women, Gender & Research, 2007)
Among diasporic Muslim Arab Sudanese a ‘citizenship tradeoff’ can be identified, whereby families move between countries which offer refugee status leading to citizenship and those whose social norms and policies support more familiar gender roles but which do not offer the possibility of naturalization. This raises critical questions about the nature of citizenship and belonging.